CHINA’S GLOBAL STRATEGY FOR THE 21ST CENTURY OF SILK ROAD: CHINA AND THE ASIA SECURITY ARCHITECTURE IN XI JINPING GOVERNMENT - Gesti Anggraini; Adi Rio Arianto; Pradono Budi Saputro (Department of International Relations Universitas Satya Negara Indonesia, 2023)
The 21st Century Chinese Silk Road has shown China a strong influence in the establishment of the Asia Security Architecture during the Xi Jinping Administration. As a regional power, China’s responsibility continues to grow during the formation of “the 21st Century Silk Road” to achieve “Chinese Dreams”. By using methodology of qualitative research with techniques of interviews, the results found that China succeeded in influencing regional countries and institutions through China's foreign and security policy strategy to changes Asia from conflict into harmony (kerukunan). These changes namely the policies to Embrace Uygurs and Taiwan, Asia and Trans-Asia Multilateralism, Peace on the Korean Peninsula, Sub-regional powers as the Asia Harmony Embryo, DOC and COC Policies in the South China Sea, SAAARC and Strategic Cooperation in South Asia, SCO and Joint Security in Asia and Across Asia, as well as BRICS and Strengthening of Inter-Regional Power Economies. This discussion is focused on (1) Asia security architecture before “the 21st Century of China Silk Road”, (2) Asia security architecture during “the 21st Century of China Silk Road”, (3) evolution of foreign policy strategies and national security policy of China “Open Door Policy”during Xi Jinping, (4) power polarization and strategic partnership in Asia, (5) China as regional power in Asia, and (6) The 21st Century Chinese Silk Road and Harmonious Asia. The result, China's influence is shown in the terms, namely: (1) the establishment of “Asia Bumisutera Dunia”, (2) formation of “Asia Benua Pemersatu”, (3) strengthening “Asia Benua Multi-Equilibrium”, (4) strengthening “Asia Benua Teduh”, and (5) strengthening “Asia Benua Harmoni.” The researchers believes that to understand the Asia Security Architecture is advisable use cross-paradigm, therefore the researchers briefly introduces paradigm, philosophy, and theory of Manunggalism through the Eastern World Relations Theories (WRT) and Mazhab Indonesia (Indonesian School) with the birth of the discipline of “Ilmu Antarbangsa (World Relations)” by mainstreaming the gotong royong World Relations System to challenge the Western International Relations Theories (IRT) that tends to anarchism system.